2016
DOI: 10.1080/13696998.2016.1187151
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of ceritinib in patients previously treated with crizotinib in anaplastic lymphoma kinase positive (ALK+) non-small cell lung cancer in Canada

Abstract: Based on the willingness-to-pay threshold for end-of-life cancer drugs, ceritinib may be considered as a cost-effective option compared with other alternatives in patients who have progressed or are intolerant to crizotinib in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The study nding is not consistent with previous studies. The Canadian study found ceritinib to be costeffective among patients who have progressed or are intolerant to crizotinib, comparing with the willingness-to-pay threshold for end-of-life cancer drugs 10 . This result may not be comparable because of the heterogeneity in study samples, drug costs, parameters, and willingness-to-pay threshold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study nding is not consistent with previous studies. The Canadian study found ceritinib to be costeffective among patients who have progressed or are intolerant to crizotinib, comparing with the willingness-to-pay threshold for end-of-life cancer drugs 10 . This result may not be comparable because of the heterogeneity in study samples, drug costs, parameters, and willingness-to-pay threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the cost-effectiveness of ceritinib. One study has speci cally evaluated its cost-effectiveness as a following treatment among patients previously treated with crizotinib in Canadian patients 10 . It suggested that ceritinib is a cost-effective option compared with other alternatives in patients who have progressed or are intolerant to crizotinib in Canada, based on the willingness-to-pay threshold for end-of-life cancer drugs.…”
mentioning
confidence: 99%
“…Prior cost-effectiveness studies comparing ceritinib to crizotinib in patients with ALK+ NSCLC have largely focused on previously treated patients. [33][34][35][36] One study in the US that examined the costeffectiveness of ceritinib compared to crizotinib in previously untreated patients with ALK+ NSCLC based on efficacy using indirect treatment comparison, showed ceritinib to be a more cost-effective treatment option than crizotinib in first line, both in short and long term. 37 However, differences exist in the healthcare systems between the US, UK and HK populations, which may translate into different resource utilization and disease management.…”
Section: Discussionmentioning
confidence: 99%
“…Prior cost-effectiveness studies comparing ceritinib to crizotinib in patients with ALK+ NSCLC have largely focused on previously treated patients. [35][36][37][38] One study in the US that examined the costeffectiveness of ceritinib compared to crizotinib in previously untreated patients with ALK+ NSCLC based on e cacy using indirect treatment comparison. The incremental cost per QALY gained was $66,064 for ceritinib versus crizotinib, showing ceritinib to be a more cost-effective treatment option in rst line.…”
Section: Discussionmentioning
confidence: 99%